Peat hydraulic properties along the gradient of oil palm ages in the tropical monsoon region - Nuraeni Dwi Dharmawati; Komariah Komariah; Suntoro Suntoro; Hermantoro Hermantoro; Azmal Hossan (Universitas Sebelas Maret, 2025)
The conversion of vast peatland areas to oil palm plantations in Indonesia may alter hydrological functions under long-term agricultural use. This study aimed to analyze the hydraulic properties of peat soil under oil palm (Elaeis guineensis Jacq.) plantations of varying ages (2–5, 6–9, and >10 years) in Ketapang, West Kalimantan, Indonesia, a region with a tropical monsoon climate. There are 27 samples gathered from 3 plantation ages in the 3 peat depths (0-20 cm, 20-40 cm, and 40-60 cm). Hydraulic properties: water holding capacity (WHC), bulk density, particle density, and porosity were analyzed using standard gravimetric, pycnometer, and oven-drying methods. Weather and environmental data from 2013–2022 were used to calculate reference evapotranspiration (ETo), crop evapotranspiration (ETc), and water balance. The results showed that hydraulic properties improved with soil depth and plantation age. WHC ranged from 400% to 850%, increasing significantly in mature plantations. Bulk density declined with depth and age, while porosity significantly increased and reached its maximum at 56.87% in older plantations. Although mature oil palms have high crop water demands (ETc), water availability remains sufficient to meet their needs. However, excess water must be properly managed to avoid reducing oil palm productivity and to preserve peat quality. These findings suggest that as oil palm matures, root development and organic residue accumulation enhance peat’s hydrological properties. This study may contribute to understanding peatland behavior under oil palm cultivation and provide crucial insight for improving irrigation and land management practices in tropical peat ecosystems.